Identity and neotypification of Hieracium zanogae (Asteraceae), endemic to the Southern Carpathians - Szelag, Zbigniew (Phytotaxa, 2016)
In a taxonomic revision of Hieracium sect. Cernua Uechtritz (1875: 215) in the Carpathians, Sudetes and Alps (Szeląg 2006a), I did not manage to resolve the taxonomic position of  H. zanogae Pax (1908: 98) described from the Retezat Mountains in the Southern Carpathians, Romania. I have been unable to trace any specimens of Pax’s original material in a number of European herbaria, including the Hungarian Natural History Museum in Budapest (BP) which hosts the Carpathian herbarium of Pax, and the Natural History Museum in Wrocław (WRSL) where Ferdinand Pax worked. Based on the description included in the protologue (Pax 1908), I supposed that H. zanogae could be conspecific with H. tubulare Nyárády in Zahn (1929: 144), the other endemic species to the Retezat Mountains.